2014
DOI: 10.1080/07399332.2014.920021
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Tract Infections in Rural Vietnam, Women's Knowledge, and Health-Seeking Behavior: A Cross-Sectional Study

Abstract: We interviewed 1,805 women in a rural setting in Vietnam with the aim of investigating women's knowledge regarding reproductive tract infections (RTIs) and their health-seeking behavior. We found that women's overall knowledge was poor. Furthermore, only one-third of the symptomatic women sought health care. RTIs affect millions of women globally each year. Most vulnerable are women in low- and middle-income countries where poverty and gender inequities affect their access to health care services. Findings fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…Delivery often causes soft birth canal injury, which in turn leads to infection. Some of our findings are consistent with previous reports [22,47,48]. Specifically, significant differences have been seen in the prevalence of STIs and endogenous infections in different socio-demographic contexts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Delivery often causes soft birth canal injury, which in turn leads to infection. Some of our findings are consistent with previous reports [22,47,48]. Specifically, significant differences have been seen in the prevalence of STIs and endogenous infections in different socio-demographic contexts.…”
Section: Discussionsupporting
confidence: 93%
“…These people often had irregular routines, high-intensity jobs, and unhealthy working environments. On the other hand, participants with higher income levels were more eager and able to improve their quality of life, including cleaner surroundings, accessible health services [48], and maintaining physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows that when patients have high health knowledge involvement, their health communication effects are better. This result is similar to Nielsen’s study (2014) which pointed out that there was significant correlation between level of knowledge and health-seeking behavior [ 36 ]. This study also revealed that when people more actively seek involvement with health knowledge and are adept at searching online for medical information, they have greater understanding of online medical information.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, studies done in Vietnam and Istanbul reported that identification of vaginal discharge as a symptom associated with suspected reproductive tract infections was poor among women (25,26). Further, another study revealed that most of the participants had no prior factual knowledge about vaginal discharge and its nature (24).…”
Section: Discussionmentioning
confidence: 98%